PENGEMBANGAN BUKU KOMIK KEBUDAYAAN SEBAGAI MEDIA MENGIDENTIFIKASI NILAI DAN ISI CERITA HIKAYAT - Aini, Irmayanti Nur; Nuryatin, Agus (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract Media is used to help the learning process in the classroom. The learning media function as a means of conveying material, overcoming the limitations of sense, space and time, and increasing students motivation. Comic books can be used as an alternative media for learning in the classroom. Because illustration in comics can increase understanding of events that have occured and may not be understood if it was read using ordinary textbooks. The comics books developed are not only focused on the material, but loads of cultural values in each story. So it is hoped that  the educational goals got by students will not only knowledge but moral education. This research uses research and development method. This study uses Borg and Gall steps which are reduced to five stages, here are (1) potential problems, (2) collection of information, (3) product design, (4) design validation, (5) design revision. They are finally able to produce comic books as media to identify the values and contents of storybooks for 10 grade.